Platinum drugs upregulate CXCR4 and PD‐L1 expression via ROS‐dependent pathways, with implications for novel combined treatment in gastric cancer - Xiaoyu Kang; Lin Zhang; Shushang Liu; Fei Wang; Haiming Liu; Fenli Zhou; Fei Wu; Haohao Zhang; Daiming Fan; Yongzhan Nie; Zhangqian Chen (The Journal of Pathology: Clinical Research)
Abstract CXC chemokine receptor 4 (CXCR4) and programmed cell death‐ligand 1 (PD‐L1) are two critical molecules involved in the tumor immune microenvironment. However, the impact of platinum drugs, such as cisplatin, on CXCR4 or PD‐L1 expression and the underlying mechanisms in gastric cancer (GC) remain unknown. Moreover, the correlation between their expression levels in GC remains elusive. Immunohistochemistry, western blot, and RT‐qPCR were performed to determine the expression pattern of CXCR4 and PD‐L1 in GC. Clinical samples, patient‐derived xenografts, and cell‐derived xenografts were utilized to investigate the effects of platinum drugs on the expression levels of CXCR4 and PD‐L1. Postchemotherapy resected GC tumor tissues showed higher CXCR4 and PD‐L1 expression levels than pretreatment biopsies (p < 0.05). Similarly, GC xenografts treated with platinum‐based chemotherapy exhibited increased CXCR4 and PD‐L1 expression levels compared to saline‐treated controls (p < 0.05). A positive correlation was detected between the expression levels of CXCR4 and PD‐L1 in GC tumor tissues. Increased levels of CXCR4 and PD‐L1 expression, in a dose‐ and time‐dependent manner upon cisplatin treatment, were observed in GC cells (p < 0.05). Cisplatin‐induced CXCR4 upregulation relies on ROS/HIF‐1α and ROS/NF‐κB pathways, while cisplatin‐induced PD‐L1 upregulation is cyclic GMP‐AMP synthase/stimulator of IFN genes‐dependent and associated with elevated ROS levels in GC cells. CXCR4 expression was found to be positively correlated with PD‐L1 expression in GC. Platinum drugs upregulated the levels of CXCR4 and PD‐L1 expression in GC. A combined strategy targeting CXCR‐4 and PD‐L1 might have clinical prospects for GC patients.